The Effective Length of Unbraced Single Story Columns - Marx, Christopher (Engineering Journal, 1976)
The AISC Manual provides the engineer with a simplified method for the design of columns in unbraced frames for stability in the form of an "Alignment Chart for Effective Length of Columns in Continuous Frames, Sidesway Uninhibited." In addition, there have been many significant papers written recently which enable engineers to achieve a greater understanding and accuracy in the design of steel columns. The effective length concept is based on the relative stiffness of the column to its bracing members. As long as these bracing members are steel, the connections are fairly standard, and the AISC Manual can be used directly with reasonably accurate results. But when the bracing member is a concrete footing, there is a choice given to the designer. The Manual states that "for column ends supported by but not rigidly connected to a footing or foundation, G ... may be taken as 10 .... If the column end is rigidly attached to a properly designed footing, G may be taken as 1.0. Smaller values may be used if justified by analysis." For multistory buildings this does not usually represent a very wide range when making a column selection. However, for single story structures, the designers choice of 1.0 or 10 will frequently result in a significant difference in total column weight. In such cases it therefore seems warranted to make a further investigation. The Alignment Chart does not provide the designer with a method of making an engineered evaluation of column bases, merely giving limit recommendations. Presented are simple and approximate methods, which allow the designer to do this. Although not included for the sake of simplicity of illustration, these methods are equally suitable for the design of columns with wind or other lateral loads.